Efficacy of acupuncture for the treatment of sciatica: A case report - Vijaykanth, S; Mangaiarkarasi, N; Prabu, P (Indian Journal of Case Reports, 2020)
Sciatica is a common type of pain affecting the sciatic nerve, a large nerve extending from the lower back down the back of each leg. Depending on where the sciatic nerve is affected, the pain may also extend to the foot or toes. We report the case of a 53-years-old male patient with sciatica pain for 1 year that started after lifting heavy weight. This case study was done to investigate the effectiveness of acupuncture for relieving sciatic pain. The treatment was given for 10 days. Gall bladder 30, urinary bladder (UB) 40 and UB 60 acupuncture points were used in this treatment. According to the findings of the visual analog scale, the pain symptom score changed from 8 to 2 after 10 days of treatment. This result has been proven the efficacy of acupuncture treatment for sciatic pain relief in this case. Under this case study, we can conclude that acupuncture techniques are beneficial to enhance the recovery stage of pain related to sciatica.